Literature review on the relationship between principal instructional leadership and teacher readiness to implement change - Abdul Aziz, Nor Azni; Foo, Say Fooi; Asimiran, Soaib; Hassan, Aminuddin (ERM Publications, 2015)
To achieve educational excellence, Malaysia has implemented various changes in the educational system. Globalisation, liberalisation, and advancements made in information technology have impelled national education policy makers to implement improvements in education policy. School-based Assessment (SBA) was introduced by the Ministry of Education Malaysia (MOE) in an effort to enhance the quality of teaching and learning processes in schools. This initiative is in line with the National Transformation Programme to produce human capital that can compete at the international level. Principals as instructional leaders are agents for pedagogical change that create a school environment conducive to learning. Past studies of organisations under reform have shown a relationship between leadership and a readiness toward change. Hence, this paper discusses the concept of principal instructional leadership and teacher readiness toward change in relation to education reform, and specifically the transition to SBA.